PROSES PEMBUATAN MESIN PENGIRIS BAHAN BAKU KERUPUK DENGAN MEKANISME GERAK TRANSLASI MENGGUNAKAN PISAU ROTASI VERTIKAL KAPASITAS 60 KG/JAM - Hutasoi, Slamat Aditia; SAM, M Danny; Mahadi, Batu; mahyunis, mahyunis; Yulfitra, Yulfitra; Kamil, M; lubis, zulkifli (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
The process of making cracker material slicing machines has the main components that want to be worked on starting from making a shaft, blade plate, inlet, outlet, engine frame, blade shield, pendulum, connecting rod, conveyor rail, and pressure rod. First stage carried out in the manufacturing process, namely identifying machine components, then making the process of making machines with several stages, namely the process of procurement of materials, measurement process, cutting process, turning process, drilling process, welding process, grinding process and workpiece assembly process. The machines used in the process of making these machine parts are cutting grinding machines, lathes, drilling machines / drilling machines, welding machines, and hand grinding machines. The number of components worked is 10 pieces, and the total number of components of the cracker slicer is 23 fruit. The time of making this machine takes 15.7 hours